Lionel Cliffe and the generation(s) of Zimbabwean politics. (22nd August 2016) - Moore, David
ABSTRACT: Lionel Cliffe's idea of 'generations' was a way of understanding the structure/agency divide and internecine struggles among Zimbabwe's nascent ruling classes during its liberation struggle. Here, its utility as an analytical tool on factional conflict is assessed. Cliffe's own involvement in the Zimbabwe African National Union's history is also examined as a lens on its generational and ideological contradictions. Further, archival evidence of the British state's observations of Mugabe illustrates how he fused the contradictions of age cohorts, points of entry into the struggle, political philosophy and international dimensions, and suggests, too, the difficulties of outsiders' understanding of complex struggles.